CONCEPTUAL MODEL FOR COVID 19 PROTOCOL’S EFFECT FOR INTERNAL SUPPLY CHAIN TO SUSTAIN COMPANY OPERATIONAL PERFORMANCE - Ermayana Megawati; Ari Heryanto; Aries Susanty; Novie Susanto (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2021)
Supply chain is an organizational system in which there are roles and perform various activities, including information, funds and other resources that are interrelated in the movement of a product or service from supplier to customer. One typical supply chain management is internal supply chain management, where is one of the integrated activities that plays an important role in the operational performance of the company, but in Covid-19 pandemic era every country including PT. AST Indonesia has implemented the Covid-19 health protocols along with their government role, WHO’s role also International Safety standard such as OHSA. Internal supply chain is composed strategic purchasing, production and distribution exactly will have affected by this health protocols. Some researchers have published many factors that influence the performance of the company like quality, flexibility, innovation but also important to study the relevant thing with Covid-19 health protocols. In this paper, we proposed a conceptual model consist of Covid-19 health protocols, strategic purchasing, production, and distribution to sustain company operational performance. AHP method is use in this research to find the dominant influencing protocol factor that affecting in making of ISCM sustainability strategy.